High Fat Diet-Induced CD8+ T Cells in Adipose Tissue Mediate Macrophages to Sustain Low-Grade Chronic Inflammation - Kiran, Sonia; Kumar, Vijay; Murphy, E. Angela; Enos, Reilly T.; Singh, Udai P. (Frontiers in Immunology, 2021)
Obesity in the United States and worldwide reached epidemic proportions within the last 20 years. Obesity is a very powerful health determinant or indicator that facilitates the development and progression of several metabolic diseases, insulin resistance, and low-grade chronic inflammation. Low-grade chronic inflammation in adipose tissue (AT) is marked by the accumulation of T cells, macrophages, and other immune cells and increased production of proinflammatory cytokines. During the onset of obesity but before the influx of macrophages, the AT is infiltrated by T cells that are strongly implicated in the initiation of obesity-associated inflammation. In comparing mice fed a high-fat diet (HFD) with those fed a normal diet (ND), we observed in HFD epididymal AT induction and infiltration of activated T cells, an accumulation and polarization of macrophages, and an increase in populations of both activated CD4+ CD8+ T cells that express CXCR3 or killer cell lectin-like receptor subfamily G member 1 (KLRG1). Levels of inflammatory cytokines and leptin and the results of in vitro co-culture experiments revealed interactions among HFD- and ND-induced CD8+ T cells, macrophages, and adipocytes. Our findings suggest that obese tissues activate and induce both CD4+ and CD8+ CD69+ T cells and augment the expression of CXCR3 receptors, which promotes the recruitment and numbers of pro-inflammatory M1 macrophages to maintain low-grade chronic inflammation. The results support the hypothesis that CXCR3-expressing CD8+T cells play an essential role in the initiation and maintenance of adipose tissue inflammation.